The effects of increasing dietary energy density on growing-finishing pig growth performance and carcass characteristics - J W Smith II; R M Musser; W B Nessmith Jr; J R Bergstrom; J A Loughmiller; Jim L Nelssen; Robert D Goodband; Michael D Tokach (Kansas Agricultural Experiment Station Research Reports, 1995)
Eighty crossbred gilts were used in a growth trial to evaluate the effects of increasing dietary energy density on growing-finishing pig growth performance and carcass characteristics. In this trial, adding fat to corn-soybean meal diets with a constant calorie: lysine ratio to increase the energy density during the growing phase (98 to 160 lb) improved feed efficiency with no influence on growth rate. However, increasing the energy content of the diet by adding fat had no benefit during the finishing phase (160 to 233 lb).; Swine Day, Manhattan, KS, November 16, 1995
Keywords: Swine day; 1995; Kansas Agricultural Experiment Station contribution; no. 96-140-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 746; Swine; Growing-finishing; Fat; Performance